A micellar sensitized kinetic method for quantification of low levels of bisphenol A in foodstuffs by spectrophotometry. Issue 7 (9th February 2017) - Temel, Nuket Kartal; Gürkan, Ramazan
Abstract : In the current study, because of its potential to leach out into foodstuffs as a result of food contact uses, a new kinetic method for the monitoring and determination of bisphenol A in foods by spectrophotometry for a fixed-time method of 5.0 min at 447 nm was established without a prior preconcentration step. Abstract : In the current study, because of its potential to leach out into foodstuffs as a result of food contact uses, a new kinetic method for the monitoring and determination of bisphenol A in foods by spectrophotometry for a fixed-time method of 5.0 min at 447 nm was established without a prior preconcentration step. The method is based on selective and rapid reduction of oxalate stabilized-Mn(iii ) with trace amounts of bisphenol A in the presence of cationic surfactants, CPC and CTAB, as both counter ion and sensitivity enhancer at pH 5.5 and 6.0, respectively. The effects of pH, concentration of reactants, reaction time, reaction temperature, and matrix components on the analytical signal were evaluated in detail, and the optimal conditions were established. There was a good linear relationship in the ranges of 2–120 μg L −1 and 5–200 μg L −1 with detection limits of 0.58 μg L −1 and 1.46 μg L −1 for CPC and CTAB, respectively. The method was validated by using two spiked quality control samples in linear working range. The samples were analyzed with a minimum 3-point calibration around the method quantification limit to minimize matrix effect. The kinetic method was successfully applied to the quantification of trace bisphenol A in the selected food samples, the intra-day and inter-day precisions as a result of stabilization of PVA were lower than 6.0% (as RSD%, n : 5), and the recoveries were quantitatively higher than 93.5% for the two quality control samples spiked with 10, 30 and 50 μg L −1 with satisfactory results.